Algal biomass to biohydrogen: Pretreatment, influencing factors, and conversion strategies. (January 2023) - Bhatia, Shashi Kant; Rajesh Banu, J.; Singh, Vijai; Kumar, Gopalakrishnan; Yang, Yung-Hun
Graphical abstract: Highlights: Algae capture CO2 and produce biomass. Algal biomass requires mild pretreatment to produce bio-sugars. Algal hydrolysate pretreatment results in less side products. It can be used as feedstock for hydrogen production in dark fermentation. Dark fermentation process can be coupled with photo fermentation and methanogenesis. Abstract: Hydrogen has gained attention as an alternative source of energy because of its non-polluting nature as on combustion it produces only water. Biological methods are eco-friendly and have benefits in waste management and hydrogen production simultaneously. The use of algal biomass as feedstock in dark fermentation is advantageous because of its low lignin content, high growth rate, and carbon-fixation ability. The major bottlenecks in biohydrogen production are its low productivity and high production costs. To overcome these issues, many advances in the area of biomass pretreatment to increase sugar release, understanding of algal biomass composition, and development of fermentation strategies for the complete recovery of nutrients are ongoing. Recently, mixed substrate fermentation, multistep fermentation, and the use of nanocatalysts to improve hydrogen production have increased. This review article evaluates the current progress in algal biomass pretreatment, key factors, and possible solutions for increasing hydrogen production.